Non-Coding RNAs and Resistance to Anticancer Drugs in Gastrointestinal Tumors - Hahne, Jens C.; Valeri, Nicola (Frontiers in Oncology, 2018)
Non-coding RNAs are important regulators of gene expression and transcription. It is well established that impaired non-coding RNA expression especially the one of long non-coding RNAs and microRNAs is involved in a number of pathological conditions including cancer. Non-coding RNAs are responsible for the development of resistance to anticancer treatments as they regulate drug resistance-related genes, affect intracellular drug concentrations, induce alternative signalling pathways, alter drug efficiency via blocking cell cycle regulation and DNA damage response. Furthermore, they can prevent therapeutic-induced cell death and promote epithelial-mesenchymal transition and elicit non-cell autonomous mechanisms of resistance. In this review we summarise the role of non-coding RNAs for different mechanisms resulting in drug resistance (e.g. drug transport, drug metabolism, cell cycle regulation, regulation of apoptotic pathways, cancer stem cells and epithelial-mesenchymal transition) in the context of gastrointestinal cancers.